PENGARUH FRAUD DIAMOND TERHADAP KECURANGAN LAPORAN KEUANGAN DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI - Edhita, Edelina Edna; Laksito, Herry (Diponegoro Journal of Accounting, 2024)
The purpose of this research is to examine fraudulent financial statement affected by fraud diamond, also the moderating effect of audit committee on construction, property, and real estate industries. Variables used in the examination are return on asset, changes in receivables, accruals, changes in auditor, changes in director as the independent variables, also fraudulent financial statement as the dependent variable. Audit committee financial & accounting expertise is the moderating variable in this examination. This research used construction, property and real estate companies during 2020-2022 with a total sample size of 228 samples. Sampling based on a purposive sampling method that follows certain criteria(s). There are two (2) analysis method used in this research, the first one is logistic regression analysis and the second one is residual analysis. The first one used for examine relationship between independent variable and dependent variable. Residual analysis used to examine the moderating variable. The results of this study indicates that changes in variable and accruals have a positive significant effect on fraudulent financial statement. Return on asset, changes in auditor, changes in director have no significant and positive effect on fraudulent financial statement. Also founded that audit committee expertise have no moderating and significant effect on relationship between return on asset, accrual, changes in auditor, changes auditor and fraudulent financial statement. Audit committee expertise founded have significant effect but no moderating effect on relationship between changes in receivables and fraudulent financial statement.